The Islamic banking and finance workbook : step-by-step exercises to help you master the fundamentals of Islamic banking and finance - Kettell, Brian (Chichester, U.K. : Wiley, 2011)
The ongoing turbulence in the global financial markets has drawn attention to an alternative system of financial intermediation: Islamic banking and finance. This is now one of the fastest growing sectors within the market place and has, so far, remained on the sidelines of this unrest. Since the inception of Islamic banking thirty years ago the number and reach of Islamic financial institutions worldwide has risen significantly. Institutions offering Islamic financial services constitute a significant and growing share of the financial system in several countries, and market participants ever.
Cover; Series; Title Page; Copyright; Dedication; Preface; About the Author; Chapter 1: What Do You Know About Islam?; 1.1 LEARNING OUTCOMES, SUMMARY OVERVIEW AND PROBLEMS; 1.2 QUESTIONS; 1.3 ANSWERS; Chapter 2: Sources of Sharia'a Law and the Role of Sharia'a Boards; 2.1 LEARNING OUTCOMES, SUMMARY OVERVIEW AND PROBLEMS; 2.2 QUESTIONS; 2.3 ANSWERS; Chapter 3: Principles of Islamic Banking and Finance; 3.1 LEARNING OUTCOMES, SUMMARY OVERVIEW AND PROBLEMS; 3.2 QUESTIONS; 3.3 ANSWERS; Chapter 4: The Murabaha Contract as a Mode of Islamic Finance.
Includes bibliographical references and index.
Print version record.
Keywords: Banking law (Islamic law) -- Problems, exercises, etc; Banks and banking -- Islamic countries -- Problems, exercises, etc; BUSINESS & ECONOMICS -- Finance; Banking law (Islamic law); Banks and banking; Islamic countries; Electronic books; Problems and exercises